Toxicity Test for Evaluating Food Safety of New Edible Seaweeds, Enteromorpha sp. and Laurencia sp. - Alim Isnansetyo; Indah Istiqomah; Retno Widaningroem; Triyanto Triyanto; Rina Anggraeni Safia; Riesa Yosita; Senny Helmiati (Universitas Gadjah Mada, 2019)
Seaweeds are potential foodstuff and source of bioactive substances that are very useful in the food and pharmaceutical industries. The objective of this study was to evaluate toxicity of aqueous extracts of seaweeds by Brine shrimp lethality test (BLT) and cytotoxicity test. The seaweeds used in this study were Enteromorpha sp. and Laurencia sp. collected from the Gunungkidul coastal line. The cytotoxicity test was performed against a normal cells line of Vero cells and a cancer cells line of HeLa cells. The cells lines were cultured in M119 medium with addition of 10% FBS and incubated at 37°C in CO2 incubator until confluent. Cells were harvested and cultured in 96 microplate with an initial density of 2x104 cells / 100 ml / well. The cells lines were treated with seaweed extracts at 24 hours after incubation. After additional 24 h incubation, the cell proliferation was observed by MTT method (3- [4,5-dimethylthiazol-2-yl] -2,5- diphenyltetrazolium bromide.The results showed that the two aqueous extract were not toxic in the BLT test, and did not exhibited any cytotoxicity activity against HeLa and Vero cells lines. Concentration-dependent cell proliferation was also not found. This results indicated that Enteromorpha sp. and Laurencia sp. extracts were no cytotoxic and might be consumed safely. These overall results suggested that the two seaweeds might be developed to be a new foodstuff for humans.